Advances in Catalytic Electrooxidation of Urea: A Review. Issue 8 (2nd June 2021) - Singh, Ramesh K.; Rajavelu, Kalaiyarasi; Montag, Michael; Schechter, Alex
Abstract : The urea oxidation reaction (UOR) is technologically important for the development of a renewable energy infrastructure. Urea electrolysis (UE) can be used to produce hydrogen much more cost‐effectively than water electrolysis, as it theoretically requires 93% less energy. Urea can also be used as fuel in direct urea fuel cells (DUFCs), instead of H2, and thus serve as an efficient hydrogen carrier. This review addresses the UOR in neutral, acidic, and alkaline electrolytes, with special emphasis on the latter. Recent developments in Ni‐based catalysts for urea oxidation (UO) in alkaline electrolytes are discussed in detail, highlighting proposed reaction mechanisms and intermediates, based on experimental and computational results. Various catalytic designs used to mitigate the UO kinetic barriers, including the use of transition metal oxides and alloys, as well as tailored surface support materials, and discuss their application in UE and DUFCs are presented. The significant challenges impeding advances in urea electrocatalysis, in addition to emerging research areas in this field, are also discussed. Abstract : Urea electrooxidation (UEO) is central to urea electrolysis and direct urea fuel cells, both of which are important components for the development of a renewable energy infrastructure. This review addresses the mechanistic aspects of UEO, the various types of UEO catalysts reported to date, and energy‐related applications thereof. It also highlights the challenges still remaining in understanding and implementing UEO.